A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.